Tourniquet use for knee replacement surgery - Ahmed, I; Chawla, A; Underwood, M; Price, A; Metcalfe, A; Hutchinson, C; Warwick, J; Seers, K; Parsons, H; Wall, P (Wiley, 2017)
This is a protocol for a Cochrane Review (Intervention). The objectives are as follows: To determine the benefits and safety of tourniquets used in knee replacement surgery.